X-ray diagnosis of mutilating arthritis in patients with psoriatic arthritis Smirnov A.V. - A.V. Smirnov (Современная ревматология, 2014)
The typical X-ray symptoms of psoriatic arthritis (PsA) in joints of hands and distal sections of feet (asymmetric lesions; isolated lesion of distal interphalangeal joints (DIJ) of hands with no changes in other small joints of hands; axial lesion of three joints in a single finger; transverse lesion of joints of the hand at the same level; destruction of distal phalanges; narrowing of the distal epiphysis of hand finger phalanges and metacarpal bones; cup-shaped deformity of the proximal portion of hand finger phalanges and narrowing of distal epiphysis; osseous ankyloses; multiple osteolytic lesions and destruction of bone epiphysis and joint deformities; inflammatory changes in the sacroiliac joints; and typical degenerative changes in the spine) are described. It is especially important to know X-ray manifestations of PsA when there are no typical cutaneous manifestations of psoriasis.